2019
DOI: 10.21608/ajs.2018.35607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substitution of Wheat Flour With Quinoa Flour on Quality of Pan Bread and Biscuit

Abstract: This study was carried out to investigate the effect of partial substitution (5, 10 and15%) of wheat flour (72% ext.) by whole meal quinoa flour (QF) on quality parameter of pan bread. QF contained the highest percentage of protein, Lipids, ash and crude fiber. Also, QF contained the highest amount of essential amino acids such as (threonine, methionine, lysine and histidine). From the results, it could be seen that, water absorption and degree of softening increased by increasing the substitution levels, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
5
8
0
Order By: Relevance
“…Previously, cookies made from composite wheat-flour and quinoa-flour showed a similar decrease in L and an increase in a* and b* (Demir & Kilinç, 2017). In bread, a similar reduction in lightness (L) and an increase in redness (a*) were observed, but the researcher also found that yellowness (b*) had the opposite effect (Moawad et al, 2019). Increased supplementation of quinoa-flour in rice-flour produced similar results in gluten-free biscuits, with a decrease in L and an increase in a* (Cannas et al, 2020).…”
Section: Color and Texture Analysis Of Cakementioning
confidence: 72%
See 3 more Smart Citations
“…Previously, cookies made from composite wheat-flour and quinoa-flour showed a similar decrease in L and an increase in a* and b* (Demir & Kilinç, 2017). In bread, a similar reduction in lightness (L) and an increase in redness (a*) were observed, but the researcher also found that yellowness (b*) had the opposite effect (Moawad et al, 2019). Increased supplementation of quinoa-flour in rice-flour produced similar results in gluten-free biscuits, with a decrease in L and an increase in a* (Cannas et al, 2020).…”
Section: Color and Texture Analysis Of Cakementioning
confidence: 72%
“…An rise in protein, lipid, and ash content was also observed in gluten-free ladyfinger biscuits when quinoa flour was supplemented to rice flour (Cannas et al, 2020). Quinoa flour had a higher quality of protein, lipids, crude fiber, and ash than wheat flour (72% extraction) (Moawad et al, 2019), which led to an increase in the nutritional quality of the composite flour and commodity (Demir & Kilinç, 2017). 7.3 ± 0.06 a 7.2 ± 0.12 a 7.5 ± 0.11 a 7.1 ± 0.08 a 7.0 ± 0.06 a 7.3 ± 0.11 a T1 7.1 ± 0.08 a 6.7 ± 0.11 a 7.1 ± 0.06 ab 6.8 ± 0.08 ab 6.7 ± 0.08 ab 7.3 ± 0.06 a T2 7.2 ± 0.11 a 7.0 ± 0.09 a 7.1 ± 00.08 ab 7.1 ± 0.08 a 7.2 ± 0.11 a 7.5 ± 0.06 a T3 6.3 ± 0.13 ab 6.3 ± 0.13 ab 6.9 ± 0.08 ab 6.8 ± 0.10 ab 6.6 ± 0.08 ab 6.8 ± 0.08 ab T4 5.7 ± 0.13 b 5.8 ± 0.14 b 5.7 ± 0.09 b 7.0 ± 0.08 a 7.1 ± 0.10 a 5.8 ± 0.14 b…”
Section: Physicochemical Quality Of Flourmentioning
confidence: 99%
See 2 more Smart Citations
“…Sirichokworrakita et al (2015) showed that moisture content of wheat flour (72%) was 11.96%, protein 11.87%, fat 1.15%, ash 0.74%, fiber 0.35%. Moawad et al (2019) mentioned that moisture content of wheat flour (72%) was 12.60%, crude protein 12.25%, lipids 0.70%, ash 0.63%, crude fiber 0.64%. This trend of results black rice flour (BRF) were obtained by Ma et al, (2018) decided that the black rice flour (BRF) contains 7.94% protein, 2.17% fat, 1.38% ash and 12.71% water.…”
Section: Chemical Composition Of Flour Materialsmentioning
confidence: 99%